Level of Acceptance in Applying Sludge as Construction Raw Materials Among Residents - Yow, Li Ping; Doh, Shu Ing; Lew, Yoke Lian (JBETE, 2016)
New technology has been introduced to the construction industry, which allowed to the reuse of sludge from wastewater treatment plant as raw material in manufacturing construction products such as concrete, brick, and aggregate. Previous studies in Germany showed that the authority introduced several measures to improve the level of acceptance of the use of sludge in the construction industry. Rather than the quality and performance of the application of sludge in the construction industry, this study is emphasizing on residents’ acceptable level of sludge as part of the materials in constructing their houses. The data came from a questionnaire survey of 170 residents in Penang and the study revealed that level of acceptance in applying sludge as construction raw material is relatively low. Only 8% of the residents agreed to apply sludge as one of the construction raw materials and half of the respondents were not willing to purchase a house that constructed by using sludge materials even though if the selling price of the house is cheaper than conventional houses. This study showed that there is urgency to improve the acceptance of the use of sludge as the replacement raw material and scientists always need to be alert with the using of material when developing new products.